Representations and social values of the profession of the teacher in basic education - Aguiar Silva, Neide de Melo [UNESP] (Univ Federal Sergipe, 2017)
This research discusses values shared by teachers of basic education in the practice of the profession, taking them as responsible for the connection between the constructs individual attitudes and social structure that act as empirical content data accessible to members of a social group and whose meanings are and can be objects of the action. Because of the research, it is possible to identify, as constituent of the teacher's training, the values of the empowerment, performance, security and self-determination. With less emphasis, are also values their desire to universalize concepts and conceptions of everyday life in society. There are signs of vocation, tradition and stimulation for the common good as naturalized values in the field of teacher training; in addition, there is evidence of a growing process in the professionalization of the teacher.
Keywords: Social values; Social representations; Teacher's training